Diagnosis of Simplex Herpes by Case-Based Reasoning Method - Marfalino, Hari; Djesmedi, Dinda; Filresi, Afandi Iddil (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Artificial Intelligence (Artificial Intelligence or AI) is defined as the intelligence shown by an artificial entity. Such systems are generally considered computers. Intelligence is created and incorporated into a machine (computer) so that it can do work as humans can. Artificial Intelligence (Artificial Intelligence or AI) is defined as intelligence shown by an artificial entity. Such systems are generally considered computers. Intelligence is created and incorporated into a machine (computer) so that it can do work like humans can. CBR method is a method used to solve a problem by using previous experience to solve a new problem. This research will discuss about Herpes Simplex, a venereal disease. In implementing this expert system, it is used by families of patients with Herpes Simplex. The goal is that the expert system can assist the patient's family in conducting the initial diagnosis process to determine the symptoms felt by sufferers of Herpes Simplex. And with the existence of this expert system can carry out appropriate treatment by sufferers of Herpes Simplex.